2013
DOI: 10.4161/psb.25891
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and rapid regeneration via multiple shoot induction from mature seed derived embryogenic and organogenic callus of Indian maize (Zea maysL.)

Abstract: An efficient method for in vitro micro propagation and genetic transformation of plants are crucial for both basic and applied research. Maize is one of the most important cereal crops around the world. Regeneration from immature embryo is hampered due to its unavailability round the year. On the contrary mature embryo especially tropical maize is recalcitrant toward tissue culture. Here we report a highly efficient regeneration (90%) system for maize by using 2 different approaches i.e., embryogenic and organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…In Bermuda grass [41] and maize [22], it has been reported that the inclusion of a low concentration of cytokinin in callus induction medium having 2,4-D promoted the induction of embryogenic callus. In our study also, the supplementation of Kinetin to callus induction medium having 2,4-D significantly increased the frequency of embryogenic callus formation,which is consistent with the results reported by Pathi et al [16] and Zhong et al [17].…”
Section: Plantlet Regenerationsupporting
confidence: 93%
See 1 more Smart Citation
“…In Bermuda grass [41] and maize [22], it has been reported that the inclusion of a low concentration of cytokinin in callus induction medium having 2,4-D promoted the induction of embryogenic callus. In our study also, the supplementation of Kinetin to callus induction medium having 2,4-D significantly increased the frequency of embryogenic callus formation,which is consistent with the results reported by Pathi et al [16] and Zhong et al [17].…”
Section: Plantlet Regenerationsupporting
confidence: 93%
“…Plant regeneration has also been reported from calli initiated from different explants, namely, anthers [2][3][4], glumes [5], immature inflorescence [6], immature tassels [7][8][9], leaf segments [10][11][12], protoplasts [13], seedling segments [14][15][16], shoot tips [17][18][19], shoot apical meristem [20], mature embryos [15,21,22], and immature embryos [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Pathi et al in 2013 reported that the maximum frequency of embryogenic callus formation (90%) was obtained on MS medium supplemented with 2 mg/l 2,4-D and 1 mg/l BAP in the dark conditions, while the compact granular organogenic callus formation (85% frequency) was obtained on MS medium supplemented with 2.5 mg/l 2,4-D and 1.5 mg/l BAP at light conditions. On the other hand, Gorji et al, 2011 using N6 medium supplemented with 2 mg/L Dicamba induced the highest frequency of organogenic callus.…”
Section: Resultsmentioning
confidence: 99%
“…Internal factors included less development of wax/cuticle layer, slight number of palisade cells, less development of vascular tissue from the roots to the shoots and minimum lignification of stem, while external factors were growth medium, humidity, light, temperature and pathogens (Gunawan 1992). The other factors affecting acclimatization were medium treatment, pot type and humidity (Pathi et al 2013). A small pot composed of a mixture of peat moss, vermiculite and sand in the ratio of 1:1:1, and the increasing humidity by covering with polyethylene bags with small hole resulted in good plant regeneration.…”
Section: Acclimatization Of Transformants and Molecular Analysismentioning
confidence: 99%